Chronic Periodontitis in Patients with Type 2 Diabetes: Analysis of the FokI Polymorphism and Perception of Quality of Life - Romário Correia dos Santos; Roberto Carlos Mourão Pinho; Renata Cimões (Association of Support to Oral Health Research (APESB), 2022)
Objective: To analyze whether the FokI polymorphism (rs228570) present in the vitamin D receptor gene in type 2 diabetics is related to chronic periodontitis's clinical status and evaluates the influence of chronic periodontitis on the perception of quality of life. Material and Methods: It is a clinical and laboratory study, composed of a sample of 59 individuals with previous diagnosis of type 2 Diabetes Mellitus and chronic periodontitis, of both sexes. On clinical examination, socio-epidemiological data and quality of life of patients with the Oral Health Impact Profile (OHIP-14) were recorded and a periogram was performed. Subsequently, saliva was collected spontaneously in sterile Falcon tubes (15 ml) and stored in the freezer at -20 °C. The purification of the genetic material was done with a PROMEGA kit (Wizard®), and the polymorphism studied was FokI (rs228570), found in the vitamin D receptor promoting region, with rs: 228570. After extraction of saliva DNA and purification, genotyping was performed by real-time PCR using specific allele probes (TaqMan® System). Results: The polymorphism of the vitamin D receptor gene was not positively associated with the severity and clinical characteristics of periodontitis, but suggested a relationship with the extent of the disease. Periodontitis also had no positive association with patients' perception of quality of life. Conclusion: The perception of quality of life of patients with chronic periodontitis and type 2 diabetes mellitus was compromised by the systemic condition, secondary to oral health, although some dimensions of OHIP-14 have been more frequently mentioned, such as psychological discomfort, physical pain and physical disability.